Investigating the Effectiveness of an Exercise Protocol for Dynamic Balance in Amateur Female Soccer Players: A Randomized Clinical Trial - Shirley Mireya Ortiz Pérez; David Marcelo Guevara Hernández; Vanessa de los Ángeles Belloso de Norieg; Fernando Daniel Álvarez Maigualema (Journal of Modern Rehabilitation)
Introduction: Women’s soccer and preventive training strategies have gained popularity in the last decade; accordingly, this study determines the effectiveness of a dynamic balance exercise protocol in amateur soccer players. Materials and Methods: A total of 24 females participated in this study and were randomly assigned to a control (n=12) and an experimental group (n=12). The experimental group received a dynamic balance exercise intervention with three weekly sessions for six weeks, while the control group maintained regular training. Balance was assessed before and after by the Y balance test in its anterior, posterior medial, and posterior lateral directions. The data were analyzed through the t-test for independent and related samples. Results: The analysis of this study shows significant improvements in dynamic balance (P=0.000) in the experimental group after the intervention of the dynamic balance exercise program for six weeks, while in the control group, there were no significant improvements. Conclusion: Dynamic balance exercise programs can be used to increase the balance of amateur female soccer players.